2021
DOI: 10.3390/ijms222111704
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Confers Plant Cadmium Tolerance: An Update

Abstract: Cadmium (Cd) is one of the most injurious heavy metals, affecting plant growth and development. Melatonin (N-acetyl-5-methoxytryptamine) was discovered in plants in 1995, and it is since known to act as a multifunctional molecule to alleviate abiotic and biotic stresses, especially Cd stress. Endogenously triggered or exogenously applied melatonin re-establishes the redox homeostasis by the improvement of the antioxidant defense system. It can also affect the Cd transportation and sequestration by regulating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 144 publications
(264 reference statements)
0
32
0
Order By: Relevance
“…As a master regulator, melatonin plays an important role in plant tolerance to abiotic stresses, such as salinity, cold, heat, drought, and heavy metals [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Our previous review systematically summarized the melatonin biosynthesis and catabolism in plants [ 19 ]. We also showed that Cd stress strongly induced melatonin accumulation via regulating the expression of genes encoding tryptophan decarboxylase (TDC), tryptamine 5-hydroxylase (T5H), N -acetylserotonin methyltransferase (ASMT), caffeic acid O-methyltransferase (COMT), and serotonin N -acetyltransferase (SNAT, also called arylakylamine N -acetyltransferase (AANAT)) [ 21 ].…”
Section: Melatonin Acts As An Antioxidant To Establish Redox Homeosta...mentioning
confidence: 99%
See 3 more Smart Citations
“…As a master regulator, melatonin plays an important role in plant tolerance to abiotic stresses, such as salinity, cold, heat, drought, and heavy metals [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Our previous review systematically summarized the melatonin biosynthesis and catabolism in plants [ 19 ]. We also showed that Cd stress strongly induced melatonin accumulation via regulating the expression of genes encoding tryptophan decarboxylase (TDC), tryptamine 5-hydroxylase (T5H), N -acetylserotonin methyltransferase (ASMT), caffeic acid O-methyltransferase (COMT), and serotonin N -acetyltransferase (SNAT, also called arylakylamine N -acetyltransferase (AANAT)) [ 21 ].…”
Section: Melatonin Acts As An Antioxidant To Establish Redox Homeosta...mentioning
confidence: 99%
“…Afterwards, melatonin enhances the tolerance via up- or down-regulating downstream regulating elements within the physiological environments of various plants ( Figure 1 , Table 1 ). The increased melatonin decreases O 2 •– and H 2 O 2 accumulation via the enhanced antioxidant enzyme activities and antioxidant levels [ 9 , 10 , 18 , 19 ]. Some examples of the various roles of melatonin in the regulation of redox homeostasis in plants under abiotic stresses are illustrated in Table 1 .…”
Section: Melatonin Acts As An Antioxidant To Establish Redox Homeosta...mentioning
confidence: 99%
See 2 more Smart Citations
“…Other than its toxicity, H 2 S has been gradually accepted as a key messenger involved in a vast number of physiologically important processes in photosynthetic organisms, such as stress resistance, autophagy, stomatal movement [4][5][6][7]. The plant itself can generate H 2 S in different subcellular sites including cytosol, chloroplasts, mitochondria, and nuclei [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%